Agri-food exports and agricultural output in selected EU member states - Strojny, Jacek (Eksport rolno-żywnościowy a produkcja rolnicza wybranych krajów UE)
This sectoral study of the largest food exporters in the EU focuses on the impact of foreign trade in products made from agricultural commodities on the prospects of agricultural output development. In particular, the study analyses the interdependencies between the output and exports of selected goods. The methodology of vector autoregression was applied to describe the analysed relationships. The results of analyses support the hypothesis about the stimulating role of exports for output and, in the case of certain countries, identify the opposite direction of the causal relationship. The impact of exports on agricultural output is of a short-term nature. Exports appear to be more exogenous than output. The degree of exogeneity of agri-food exports is lowest in the Netherlands
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 1, s. 173-186